Relationship between Economic Growth, Renewable Energy Consumption and CO2 Emission in Nordic Countries: A Panel data cointegration Analysis - Cagetti,Dario (2024)
The increasing relevance given to climate change and sustainable growth has raised the need to analyse the linkage between the environment and the economy. This study investigates the causal relationship between economic growth, CO2 emissions, and renewable energy consumption. It specifically uses data from 1966 to 2022 from the Nordic countries, which, with their progressive environmental policies and commitment to sustainable development, serve as an ideal case study. The causal relationship between variables is examined using Granger causality test in VECM framework. Results of unit root tests show that all variables are non-stationary in their level form and stationary in first difference form. Cointegration is found between the variables, revealing the presence of a long-term relationship. Granger causality tests are implemented to investigate short-term connections. The results suggest the existence of bi-directional causality between economic growth and CO2 emissions and between CO2 emissions and renewable energy consumption. The empirical results also indicate no short-term causality between economic growth and renewable energy consumption.
Keywords: Economic Growth; Renewable Energy; CO2 emissions; Granger causality; Nordic countries